Analisis Strategi Pemasaran Program Haji Dan Umroh Dalam Menarik Minat Jemaah Pada PT UD Tour dan Travel Universal Di Majalengka - Siti Nur Azizah,; Lestari, Ayu Gumilang (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
This study aims to analyze the marketing strategies implemented by PT. UD Tour and Travel Universal in attracting prospective Hajj and Umrah pilgrims in the Majalengka region. In the face of increasing competition in the religious travel industry, companies are required to adopt effective marketing strategies to enhance competitiveness and expand market share. This research uses a qualitative approach with data collection techniques including interviews, observations, and documentation. The results indicate that the company’s marketing strategy involves the marketing mix: product, price, place, and promotion. PT. UD Tour and Travel Universal focuses on providing high-quality services, competitive pricing, a strategic location, and promotional activities through social media, customer testimonials, and partnerships with local religious leaders. These strategies have proven effective in increasing the interest and trust of prospective pilgrims. The study concludes that a well-executed marketing strategy combined with professional service delivery is key to successfully attracting prospective Hajj and Umrah pilgrims.